2016
DOI: 10.1177/1049732315627644
|View full text |Cite
|
Sign up to set email alerts
|

HIV’s Syndemic Links With Mental Health, Substance Use, and Violence in an Environment of Stigma and Disparities in Japan

Abstract: A syndemics orientation has become a valuable lens through which to understand the complex system dynamics of HIV, HIV's links to other social and health problems, and the design of effective, comprehensive interventions. Using data from a broader ethnographic study of HIV epidemics in the Kansai Region and Tokyo Metropolitan Area of Japan, I found that HIV was synergistically linked with poor mental health, substance use, and violence, suggesting the existence of at least three syndemics. These occurred in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 51 publications
1
11
0
1
Order By: Relevance
“…My findings related to stigma were grounded in an especially large amount of data and related to a larger literature on HIV syndemics. This merited detailed treatment in a separate paper ( DiStefano, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…My findings related to stigma were grounded in an especially large amount of data and related to a larger literature on HIV syndemics. This merited detailed treatment in a separate paper ( DiStefano, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…A focus of the comparatively smaller body of social science research, including both qualitative and quantitative investigations, has been the experiences of a very specific population: the victims and families affected by the “Yakugai AIDS Scandal,” in which hemophilia patients were infected through blood products imported mainly from the U.S.( Cullinane, 2005 ; Mizota, Ozawa, Yamazaki & Inoue, 2006 ; Seki, Kakinuma, Kuchii & Ohira, 2015 ; Seki, Yamazaki, Mizota & Inoue, 2009) . The scandal and its aftermath have been an important part of Japan's unique HIV history; however, hemophiliac HIV cases have comprised only 5.9% of cumulative HIV/AIDS cases in Japan since the beginning of the epidemic ( Ministry of Health Labour and Welfare, 2014 , Japan Foundation for AIDS Prevention, 2013a , DiStefano, 2016 ). Other studies, published in virtual isolation mainly by anthropologists, sociologists, and some economists, have examined HIV and sexual politics ( Miller, 2002 ); a clinical phobia of HIV among uninfected persons ( Miller, 1998 ); sexual activities and social relationships among persons living with HIV ( Inoue, Yamazaki, Seki, Wakabayashi & Kihara, 2004 ); sex partner-seeking strategies among MSM;( Ishi, 2012 ) motivators and deterrents of HIV testing ( Takahashi, Yamazaki & Kawata, 1999 ); and the economic impact of antiretroviral therapies ( Kimura, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…Further, GBD was often accompanied by violence. This pattern is not unique to Brazil; numerous studies globally have shown how TGW report frequent experiences with physical [ 8 , 43 47 ], verbal [ 8 , 43 47 ], symbolic [ 44 , 48 , 49 ], emotional [ 8 ], and sexual violence [ 16 , 43 , 50 54 ]. The mixed-methods data show that GBD is a complex phenomenon in Brazilian society: the quantitative data showed that it can influence the use of condoms in sex with stable sexual partners, and the qualitative data suggested that the trust that TGW feel for their stable partners can also increase their willingness to have sex without a condom.…”
Section: Discussionmentioning
confidence: 99%
“…No caso das mulheres transgêneras, esse traço é a identidade de gênero, o que impossibilita que outros atributos tenham atenção, imputandolhes descrédito 26 e discriminação, que, por sua vez, produz desfechos negativos de saúde. O estigma e a discriminação, por exemplo, estão geralmente associados com a exclusão social, a baixa escolaridade 15,27,28 e com as barreiras no acesso ao mercado de trabalho 20,27,28 , podendo influenciar a entrada dessas pessoas no mercado sexual 20,27,28 e a adoção de comportamentos de risco para doenças e agravos, como o uso de substâncias injetáveis sem orientações médicas e o sexo anal desprotegido com parceiros sexuais 29 ; também com desfechos psiquiátricos (como ansiedade e depressão) 20,30 e uso de substâncias psicoativas 30,31,32 .…”
Section: Introductionunclassified